A Model for the Development of Participatory Fire Protection and Suppression Engineering Systems - Phra Suthirattanabundit; Suksanguan, Norpong (Journal of Public Administration Chiang Rai Rajabhat University, 2023)
“Knack” This is due to the process of participatory fire protection engineering system development model. It is an action that participates in every step of the process of the development model. From the design process of the development model the organization of the process of the development model; and evaluation of the process organization of the development model. to meet or to achieve a goal Characteristics of the learning process based on the fire prevention and suppression engineering system as the center, the development of the learning process is a process that corresponds to the way of life, social context, environment and culture of the fire prevention and suppression engineering system. The process of creating change by stimulating the search for knowledge to be curious, to learn, as well as not to judge things from the phenomena seen before contemplating the causes, origins and conditions involved When the fire prevention and suppression engineering system can create its own knowledge have discovered the truth for themselves Able to think with a sense of freedom without fear (intellectual) and dare to change internally. The quantity of knowledge, thoughts, attitudes, values, consciousness, etc., and externally include behaviors, skills, and expertise.